Detection of Intestinal Cancer by Local, Topical Application of a Quenched Fluorescence Probe for Cysteine Cathepsins. Issue 1 (22nd January 2015) - Segal, Ehud; Prestwood, Tyler R.; van der Linden, Wouter A.; Carmi, Yaron; Bhattacharya, Nupur; Withana, Nimali; Verdoes, Martijn; Habtezion, Aida; Engleman, Edgar G.; Bogyo, Matthew
Summary Early detection of colonic polyps can prevent up to 90% of colorectal cancer deaths. Conventional colonoscopy readily detects the majority of premalignant lesions, which exhibit raised morphology. However, lesions that are flat and depressed are often undetected using this method. Therefore, there is a need for molecular-based contrast agents to improve detection rates over conventional colonoscopy. We evaluated a quenched fluorescent activity-based probe (qABP; BMV109) that targets multiple cysteine cathepsins that are overexpressed in intestinal dysplasia in a genetic model of spontaneous intestinal polyp formation and in a chemically induced model of colorectal carcinoma. We found that the qABP selectively targets cysteine cathepsins, resulting in high sensitivity and specificity for intestinal tumors in mice and humans. Additionally, the qABP can be administered by either intravenous injection or by local delivery to the colon, making it a highly valuable tool for improved detection of colorectal lesions using fluorescence-guided colonoscopy.